Tom e Vinícius na Alvorada: um prisma geográfico - Taoni, Lucas Jurado [UNESP]; Cunha, Fabiana Lopes da [UNESP] (My University, 2013)
This article has been generated by the interface between geography and music. Methodologically, we have used a multidisciplinary bibliography that contemplates cultural geography, history, music, linguistics, literature, anthropology, for we understand that, for the understanding of a polysemous code, as it is in music, we need a diversity of looks. Our main document for an analysis of the construction of Brasília is the “Sinfonia da Alvorada” (Symphony of the Dawn), composed by Antônio Carlos Jobim and Vinícius de Moraes. Here, we attempt mainly to do a textual analysis of the work under an external perspective of the symphonic work, we mean, analyzing more its semantics (considering the product between interlocution and interpretation), and less its instrumental aesthetics, although the latter is also present. Finally, we attempt to understand the connection that exists between the actors and the spaces which are metamorphosing along with the construction of the city and which puts into evidence the idea of social circularity, proposed by the “Sinfonia da Alvorada”. This piece captures social and cultural elements related to the construction of Brasília and repositions and rearranges it through the execution of the music, in such a way that this arrangement can provide a change in the senses which are constructed from the urban experience in Brasília.

Este artículo fué generado a partir de la interface geografía y música. Metodologicamente utilizamos una bibliografia multidisciplinar y que contempla la geografia cultural, historia, música, lingüística, literatura, antropología, pues entendemos que para La comprención de um código polisemico, como es el caso de La música, precisamos de una diversidad de interpretaciónes. Nuestro principal documento de análisis para La discución de La construcción de Brasilia es la “Sinfonía de la Alvorada”, de autoría de Antonio Carlos Jobim, y Vinicius de Moraes. Buscamos aqui hacer principalmente um analisis textual, sobre uma perspectiva externa de la obra sinfónica, ésto es, analisando mas su semántica (considerando los entredichos entre interlocución e interpretación) y menos su estética instrumental, fuera ella también este presente. Buscamos, finalmente comprender la conección que hay entre los actores y los espacios que se están metamorfoseando com la construcción de la ciudad y que pone en evidencia la Idea de circularidad social, que es expuesta por la Sinfonía de la Alvorada.Tal composición capta elementos sociales y culturales acerca de la construcción de Brasilia y los recoloca a traves de la ejecución de la música, de manera que ese rearranjo puede propiciar um cambio sobre los sentidos construídos a partir de la experiência urbana em Brasilia.

Este artigo foi gerido a partir da interface geografia e música. Metodologicamente utilizamos uma bibliografia multidisciplinar e que contempla a geografia cultural, história, música, linguística, literatura, antropologia, pois entendemos que para a compreensão de um código polissêmico, como é o caso da música, precisamos de uma diversidade de olhares. Nosso principal documento de análise para a discussão da construção de Brasília é a “Sinfonia da Alvorada”, de autoria de Antônio Carlos Jobim e Vinícius de Moraes. Procuramos aqui fazer principalmente uma análise textual, sob uma perspectiva externa da obra sinfônica, isto é, analisando mais sua semântica (considerando os interditos entre interlocução e interpretação) e menos sua estética instrumental, embora ela também esteja presente. Buscamos, enfim, compreender a conexão que há entre os atores e os espaços que estão se metamorfoseando com a construção da cidade e que põe em evidência a ideia de circularidade social, que é exposta pela Sinfonia da Alvorada. Tal composição capta elementos sociais e culturais acerca da construção de Brasília e os recoloca e rearranja através da execução da música, de modo que esse rearranjo pode propiciar uma mudança sobre os sentidos construídos a partir da experiência urbana em Brasília.
Keywords: Cultural Geography; Brasilia; Sinfonia da Alvorada; Tom Jobim e Vinícius de Moares; Geografía Cultural; Brasilia; Sinfonía de la Alvorada; Tom Jobim y Vinicius de Moraes; Geografia Cultural; Brasília; Sinfonia da Alvorada; Tom Jobim e Vinícius de Moraes